Design and examine oligonucleotide structures as inhibitors to topoisomerase IV - Guo, Juanjuan (2014)
Topoisomerase IV is an enzyme that exclusively presents in prokaryotic cells and is mainly responsible for unwinding interlocked DNA strands at the final stage of prokaryotic replication. Since it is a prokaryotic enzyme, various types of quinolones were developed in the past as inhibitors of topo IV for treating bacterial infection. In consideration that bacterial resistance to antibiotics has occurred constantly, new types of oligonucleotides as topo IV inhibitors have been examined during our recent investigations, which include those that contain nick sites, gap, mismatched and overhang structures. Among them, the nick-, gap- and mismatched base pair-containing oligonucleotides displayed significantly high inhibitory effects toward topo IV. It is our anticipation that the outcomes of our investigation could be beneficial for pharmaceutical companies for evaluating the possibility of topo IV oligonucleotide inhibitors as antibiotics once tools for transfection of oligonucleotides into bacteria will be validated in the future.